PERAN KARANG TARUNA DALAM MENINGKATKAN KEPEDULIAN SOSIAL MASYARAKAT DI DESA GIRIHARJA KECAMATAN CIPANAS LEBAK-BANTEN - Anggun Solihah (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
The purpose of this study is to explain the role of youth organizations in increasing the social awareness of youth at the village of Giriharja. The research method used in this study is a qualitative descriptive method. The subjects of this study are the members of the youth organization. With data collection techniques, namely through observation and interviews. The research location is in the village of Giriharja which was conducted from September until November 2020. The results of this study indicate that the role of the Youth Organization in increasing youth social awareness is in the unfavorable category. This means that youths who lack responsiveness, care, are indifferent to the surrounding environment and cool with their own world so that they forget their duties as youths and members of the youth organization. Therefore, youth are expected to be more concerned with their duties and also care for the surrounding community.